1991
DOI: 10.1111/j.1532-5415.1991.tb01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyposomatomedinemia in Men with Post‐Poliomyelitis Syndrome

Abstract: The age of onset of the post-poliomyelitis syndrome (PPS) coincides with the tendency for declining activity of the growth hormone/somatomedin C (GH/SmC) axis. The normal plasma SmC range in men before the age of 40 is 0.50 to 1.50 units/mL. After age 40 about 30% of men have a plasma SmC level below 0.35 units/mL, signifying no detectable spontaneous GH secretory pulses. Because the GH/SmC axis stimulates DNA, RNA, and protein synthesis in muscle cells and increases their size and number, a deficiency of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
5
2
Order By: Relevance
“…In the present study, mean levels of IGF-1 in patients were not abnormal and there was no significant correlation between IGF-1 levels and maximal 31,33 A recent study reports a negative correlation between muscle force and IGF-1 levels. 38 Serum creatine kinase levels were mildly increased in prior-polio patients.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In the present study, mean levels of IGF-1 in patients were not abnormal and there was no significant correlation between IGF-1 levels and maximal 31,33 A recent study reports a negative correlation between muscle force and IGF-1 levels. 38 Serum creatine kinase levels were mildly increased in prior-polio patients.…”
Section: Discussioncontrasting
confidence: 66%
“…It remains to be determined whether decreased levels of IGF-1 are linked to impairment in voluntary activation in these patients and whether the maximal level of voluntary activation improves when IGF-1 levels are increased. 31,33,35,38 Some investigators 40,42 have found increased serum creatine kinase levels in postpolio patients. Therefore, we hypothesized that IGF-1 and creatine kinase may predict impaired voluntary activation and impaired endurance, respectively.…”
mentioning
confidence: 97%
“…In a pilot study of 10 PPS patients Shetty KR et al [17] reported the mean serum [IGF-I] to be approximately 50% lower than age matched controls. A larger study by Rao et al [18] of 124 PPS patients and 261 age matched controls also reported a 25% lower mean [IGF-I] in the PPS patients.…”
Section: Discussionmentioning
confidence: 97%
“…The absence of detailed information on the endogenous peripheral IGF system in disease states may be one of the limitations in the design of these clinical trials. To date, conflicting studies of the circulating IGFs report normal or decreased levels of IGF-I in ALS [13][14][15] and post polio syndrome (PPS) [16][17][18] but unchanged levels of IGF-I in MS [14,[19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…In 1990, the authors found the plasma IGF‐I level to be low in patients with the post‐poliomyelitis syndrome compared with age‐matched controls 10 . They then found that the decreased IGF‐I in these individuals was associated with low or absent levels of nocturnal serum GH 11 .…”
mentioning
confidence: 99%